Extracellular K+ and Ca2+ activities measured during the action of negative pressure under a suction electrode placed on the surface of frog heart ventricle - Slavícek, J; Vyskocil, F (Physiologia Bohemoslovaca, 1985)
The application of negative pressure of -40 kPa (-300 mm Hg) for 10 min under a suction electrode placed on the surface of the spontaneously beating frog ventricle changed the extracellular potassium activity (aoK+) in three phases: a phase of rapidly rising aoK+, a slowly decaying phase and a phase of slowly rising aoK+. The changes reversed when suction was discontinued during the rapidly rising and decaying phase, but were not reversed during the slowly rising phase. Calcium extra-cellular activity (aoCa2+) decreased between -5 and -13 kPa, but increased during the higher pressures. The results indicated that injury of the ventricular tissue caused by a suction electrode elevated aoK+ and altered aoCa2+.
Keywords: Animals; Heart; draslík; extracelulární prostor; Suction; Heart Ventricles; membránové potenciály; Decerebrate State; Potassium; reakční čas; Action Potentials; Extracellular Space; srdeční komory; srdce; odsávání; vápník; Electrodes; Calcium; decerebrační rigidita; Reaction Time; elektrody; Rana temporaria; zvířata; akční potenciály; Membrane Potentials